Assessment of Osteogenesis Enhancement in Rats Using Bone Densitometry: An In Vivo Study - Hassan, Manar Abd Alrazaq; Ajwad, Asmaa A. (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Human survival depends on the availability of water. Safe drinking water is a fundamental human right as well as a basic need for a good health. At the mineral and organic levels of water composition, exposure to electromagnetic fields can cause considerable changes in the quality of drinking water. As a result, water is more easily absorbed into the cell walls throughout the body, making it better suited for organ growth and development. When drunk on a daily basis, magnetic water causes dramatic changes in bone mineral density and content. Due to the necessity for distinct beam filtering and near-perfect spatial discography of the two attenuations, DXA (DualEnergy X-ray Absorptiometry) was included with general-purpose X-ray systems. In rats that drink magnetized water on a daily basis, the DXA can be used to calculate the weight and area of all head compartments. Objective: By employing a Bone Densitometry scan on the head regions of rats, this study aims to assess the changes in the rat's skull bone measures (area, weight, bone mineral content, and bone mineral density) after feeding the animal with magnetized water. Methods: This study involved thirty adult male rats (6 weeks old). For 30 days, 15 rats were given a magnetized water to drink and used as experimental animals. For comparison purposes, the remaining 15 rats were given regular water for 30 days. After the experimental procedure was done, each rat's head was scanned with a DXA to determine bone weight, area, bone mineral content, and bone mineral density. Before drinking water, each rat in both the experimental and control groups was examined. The head of each rate was scanned using a DXA to get the values of bone: weight, area, mineral density, and mineral content after 30 days of consuming magnetized water. The four bone measures were statistically compared in the experimental and control rats, p-values below 0.05 were considered significant. Results: Comparing to control rats, experimental rats showed a significant increase in the bone’s weight and area of the skull (p<0.05, Wilcoxon test). Bone marrow content and bone marrow density enhanced significantly as well in experimental rats after drinking the magnetized water for 30 days. Conclusions: Drinking water that has been subjected to electromagnetic fields for 30 days can improve bone marrow content and density in rats. Drinking magnetized water also has a substantial impact on bone mass and area.